Kinerja Struktur Sistem Tunggal dan Ganda dengan Performance Based Design - Siti Aisyah Nurjannah; Hanafiah; Wanda Lestari; Erwin Lim; Iswandi Imran (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
The structure of a simple rental apartment building of the Sumatran Technology Institute had been modeled using the Performance Based Design method. The aim of this study was to obtain the base shear and maximum displacement as well as the performance level of the building structure models in resisting the combination of gravitation and lateral earthquake loads. The loads were based on the function and location of the building. The building structures had been designed as a double system, namely the beam-column frames and shear walls in the direction of the XZ and YZ axis. There were four models: the models with a double system according to the original design, the beam-column frames without XZ shear walls, the beam-column frames without YZ shear walls, and the beam-column frames without shear walls. The results of the analysis at the performance level showed that the model with a double system was able to resist the highest base shear while the frames system without shear walls was only able to resist the lowest base shear compared to other models. The inter story drift under earthquake loads in the direction of the X and Y axis showed that all models of structural system were still within the safe limit.